2023
DOI: 10.1103/physrevb.107.064207
|View full text |Cite
|
Sign up to set email alerts
|

Quantum states in disordered media. II. Spatial charge carrier distribution

Abstract: The space-and temperature-dependent electron distribution n(r, T ) determines optoelectronic properties of disordered semiconductors. It is a challenging task to get access to n(r, T ) in random potentials, avoiding the time-consuming numerical solution of the Schrödinger equation. We present several numerical techniques targeted to fulfill this task. For a degenerate system with Fermi statistics, a numerical approach based on a matrix inversion and that based on a system of linear equations are developed.For … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…So far, we considered here degenerate systems with Fermi statistics. In Section 3, we address a complementary case of a non-degenerate system with Boltzmann statistics, following two recent studies [13,14]. While in those studies, hundreds of equations were used to treat the non-degenerate case, we demonstrate in this paper that the essence of the theory for Boltzmann statistics can be introduced using only several equations.…”
Section: Methods 2: Solving a System Of Linear Equationmentioning
confidence: 99%
See 3 more Smart Citations
“…So far, we considered here degenerate systems with Fermi statistics. In Section 3, we address a complementary case of a non-degenerate system with Boltzmann statistics, following two recent studies [13,14]. While in those studies, hundreds of equations were used to treat the non-degenerate case, we demonstrate in this paper that the essence of the theory for Boltzmann statistics can be introduced using only several equations.…”
Section: Methods 2: Solving a System Of Linear Equationmentioning
confidence: 99%
“…In the LLT, the random potential is converted into some effective potential, drastically simplifying the calculations. However, recent studies [13,14] revealed substantial problems of the LLT. For instance, the effective potential in the LLT lacks the temperature dependence, which is necessary to describe n(r, T) appropriately.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that there are indirect methods investigating the essential aspects of electron states in disordered structures without solving explicitly the Schrödinger equation, such as the localization landscape theory [25][26][27] or the low-pass filter approach [28,29]. However, since the energy band structure is one of our interests here, we focus on direct band-structure calculation methods.…”
Section: Introductionmentioning
confidence: 99%